ANALISIS BUDAYA MUTU UNIVERSITAS SURABAYA DALAM RANGKA PENGUKURAN EFEKTIVITAS PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 - Swaputri, Naya Adi; Rosiawan, Muhammad; Hadiyat, M. Arbi (University of Surabaya, 2014)
University of Surabaya is a college that implement ISO 9001. However, theapplication of ISO 9001 will be successful if supported by organizational culturechange in a positive direction. Total Quality Management or the development ofquality culture requires line managers to change the style, way of working andeven behavior as far as possible in order to get out of traditional organizationalstructures. It is necessary for testing to determine the extent of the influence ofISO 9001 at the University of Surabaya against existing quality culture in theorganization by the method of Structural Equation Modeling (SEM). The purposeof this study was to measure the quality culture, knowing the relationship ofcultural change with the implementation of ISO 9001 quality, and providesuggestions for improvement in organizational performance UBAYA thus beeffectively and efficiently and to create a cultural change that brings qualityUBAYA towards positive direction. Results obtained from this research is theapplication of ISO 9001:2008 proven direct impact positively on the quality ofcultural change in UBAYA of 50.04 % . The results of the questionnaire and thegreat close relationship models that will be used as a reference in determining therepair using the method of Quality Function Deployment . Variable ISO 9001 thatmust be fixed first is the management system approach with a weight of 0.341 ,the second is the process approach with a weight of 0,332 and the latter isemployee engagement with a weight of 0.326 . From the results obtained QualityFunction Deployment major repairs done by looking at the importance of how thevalue of more than 636.19875 . The improvement of priority is establishingquality objectives in accordance with the vision and mission UBAYA , distributetasks employees are multitasking in a single unit of work , and make theeffectiveness of the program with clear criteria and involving all employees.